TDP-43-mediated amyotrophic lateral sclerosis: new/hidden insights from Drosophila - Colaianni, Davide; Ceccato, Nadia; Antolini, Pietro; Conte, Carmela; De Pittà, Cristiano; Feiguin, Fabian; Mazzotta, Gabriella M. (Frontiers in Cell and Developmental Biology, 2025)
Transactive response DNA-binding protein 43 (TDP-43) is a key factor in motor neurons and related neurodegenerative disorders, and the presence of cytoplasmic aggregates of TDP-43 is a major hallmark of diseases such amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Nevertheless, little is known about early developmental effects or the systemic nature of TDP-43-mediated pathology. Drosophila melanogaster is acknowledged as a powerful genetic model for studying the genetic inheritance and the behavioral and developmental processes associated with human neurodegenerative diseases, including ALS. To better understand the possible roles and potential pathogenic mechanisms of TDP-43 protein in the pathogenesis of ALS, we performed a transcriptomic analysis of larvae from a Drosophila model knock-out (KO) for the TBPH gene, the fly TDP-43 ortholog. Interestingly, the Gene Ontology (GO) analysis highlighted some pathways not yet associated with this pathology and this model. We identified several genes encoding for serine proteases, a class of enzymes that in the central nervous system (CNS) play important roles in neural development, synaptic plasticity, and neurodegeneration. Our work provides insights into novel pathological mechanisms underlying the disease, thereby opening new pathways for drug discovery.